Socio-psychological correlations of youth addiction on social networks - Sheinov, Victor P.; Bubnau, Yury M.; Yermak, Vladislav O.; Gribanovsky, Sergey P. (Journal of the Belarusian State University. Sociology, 2022)
Addiction of boys and girls from social networks is associated with the presence of their feelings of loneliness, as well as anxiety, depression, stress, dissatisfaction with life, impulsivity, narcissism, weak assertiveness, low self-esteem, insecurity from cyberbullying. The purpose of this study is to test the hypothesis about the possible connections of the addiction of young people from social networks with their self-confidence, emotional intelligence and style of behaviour in conflict situations. The empirical study was based on the data of an online survey of 265 respondents, including 117 boys and 148 girls. Dependence on social networks was measured by the ZSS-15 questionnaire (V. P. Sheinov, A. S. Devitsyn), self-confidence – by the method of V. G. Romek, emotional intelligence – by the Thomas – Kilmann test, dependence on a smartphone – a short version of the SAS-16 of the questionnaire «Scale of dependence on a smartphone» (V. P. Sheinov). The article found that boys and girls have statistically significant negative associations of addiction from social networks with self-confidence and positive connections with dependence on a smartphone and with all the factors that form it (loss of control over themselves, fear of losing a smartphone and euphoria from its use). It is shown that it is the psychological problems of young people that are the main reason for the occurrence of one or another degree of addiction from social networks. At the same time, the need of young men and women in communication is satisfied if they have addiction to a lesser extent than the factors «psychological state» and «obtaining information». Neither boys nor girls have been found to link social media addiction to social contact initiative. The social media addiction of young men is negatively correlated with their social courage and positively correlated with their reaction to conflict in avoidance mode. Such correlations in girls have not been recorded. In boys and girls, there are various correlations of addiction from social networks with emotional intelligence: in boys – a negative connection with self-management, in girls – a positive connection with the recognition of emotions of other people. In general, girls are more dependent than boys on social media. These results are new, as neither domestic nor foreign publications have found results on the links of social media addiction to components of emotional intelligence.
Keywords: youth dependence on social networks; self-confidence; emotional intelligence; behaviour in conflict situations; dependence on a smartphone; addiction factors; girls; boys